Skellefte mining district in 3D : results from integrated interpretation of potential field, resistivity/IP and reflection-seismic data - Tavakoli, Saman; Bauer, Tobias; Skyttä, Pietari; Elming, Sten-åke; Thunehed, Hans; Weihed, Pär (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2012)
Located in northern Sweden, the Skellefte mining district has been subject to several geological and geophysical investigations, as it is hosting abundant volcanic-hosted massive sulfide deposits. The importance of mineral exploration at greater depths in the Skellefte District has been increased since most of mineralization at shallow depths are already discovered and exploited. Therefore, geophysical methods become particularly important as they can improve our knowledge about spatial relationship between geological features at the depth. In the first part (local-scale) of this study, we used resistivity/IP data to map the subsurface geometry down to 430m. Furthermore, the results of the resistivity/IP studies were constrained with potential field data down to 1.5 km depth. In the second part (Regional-scale), potential field data were used to constrain the interpretation of the reflection-seismic data down to 5 km depth. The result from the first part indicated a good correlation between the initial resistivity model and the magnetic and gravity field calculated from that model. In Part II, the gravity and magnetic data were investigated to better understand the contact between the Skellefte Group,volcanic rocks and the Bothnian Basin sedimentary rocks. Furthermore the method was used to constrain the geometry of late-orogenic gabbro-diorite and granite intrusions which occur along inferred shear zones that are only poorly indicated, or not visible at all on the reflection-seismic profiles. As the main outcome, the proposed integrated 3D model of the central Skellefte District (CSD) revealed crucial information about the spatial relationship between key lithologies which will be further used to understand the evolution of CSD in the 4th dimension, time. Godkänd; 2012; 20111106 (samtav)